Recherche de substances naturelles issues de plantes médicinales marocaines capables d'inhiber la prolifération des cellules cancéreuses du col de l'utérus et étude de leurs mécanismes d'action - Merghoub, Nawal (Université Mohammed V - Agdal, Faculté des Sciences, Rabat, 2011)
Worldwide, the discovery for new anticancer drugs remains one of main concerns of the researchers in oncology. Plants were at the origin of many active molecules having shown their efficacy in the treatment of various cancers. In Morocco, traditional medicine, rich and diverse, constitutes an important source for screening of new potentially bioactive molecules with therapeutic potential. In this context, and in order to promote Moroccan medicinal plants, the aims of this study is the search for new natural substances from plants used in traditional medicine Moroccan, able to inhibit the proliferation of cervical cancer cells. Seven medicinal plants were selected, on the basis of an ethnobotanical study and according to their uses in traditional medicine, and evaluated for their cytotoxic effects against two cervical cell lines HeLa and SiHa. Among these plants, Inula viscosa L. and Retama monosperma L. have a particular interest. The hexanic extract (IV-HE) and dichloromethane fraction (IV-DF) from Inula viscosa L. and dichloromethane fraction from Retama monosperma L. (Rm-DF) induce a significant cytotoxic activity against the two cell lines after 72h of treatment, with IC50 values ranging from 6 to 22 µg/ml. Subsequently, we were interested in studying the mechanisms of action of these extracts. IV-HE, IV-DF and Rm-DF induce cell death by apoptosis, as evidenced by pro-caspase 3 cleavage, caspase 3 activity and PARP cleavage. Moreover, these extracts induce a decrease in mitochondrial membrane potential (ΔΨm) and increase of reactive oxygen species (ROS), accompanied by a decrease in anti-apoptotic protein Bcl-2 expression, suggesting that apoptosis induced by these extracts requires mitochondrial events. We show also that IV-HE and IV-DF extracts were able to significantly inhibit telomerase activity after 48 hours treatment, by using the Telomerase amplification protocol (TRAP) analysis. These data were confirmed by TAGGG telomere length assay. Moreover, the study of the multidrug-resistance (MDR) status of IV-HE, IV-DF and Rm-DF extracts was performed using different cell lines expressing MDR genes. The resistance index of IV-HE and IV-DF extracts was less than 2-fold, suggesting that the molecules contained in these extracts are not MDR substrates. The bio-guided fractionation of hexanic Inula viscosa extracts (IV-HE), has allowed the purification of a sesquiterpene lactone, tomentosin. This molecule was found to inhibit significantly the growth of SiHa and HeLa cervical cancer cell lines in dose and time-dependent manner (IC50 values of 7.10 ± 0.78 µM and 5.87 ± 0.36 µM, respectively after 96h of treatment). TTAGGG telomere length assay had shown that tomentosin induces significantly a telomeric G-overhang shortening in SiHa and HeLa cells in dose-dependent manner. This study provides the first evidence that tomentosin targets telomere machinery and induces apoptosis in cervical cancer cells. The molecular mechanism underlying tomentosin-induced apoptosis may involve a mitochondria-mediated signaling pathway. Tomentosin induces also a cell cycle arrest of SiHa and HeLa cells in G2/M phase. All these data suggest that Inula viscosa L. and Retama monosperma L. have a high potential for the development of news anticancer agents.
Keywords: Biologie; Biochimie; Immunologie; Plante médicinale; Inula viscosa L.; Retama monosperma L.; Tomentosine; Cytotoxicité in vitro; Apoptose; Télomère; Télomérase; Cancer du col utérin